An Analysis of Distance Learning at the English Department of UMK: Students’ Social Presence and Sense of Classroom Community - Rabiatul Adawia; Aderlaepe Aderlaepe; Deddy Amrand (Journal of Language Education and Educational Technology (JLEET), 2024)
The objective of this study is to assess the extent of students’ social presence and their perception of classroom community in the context of distance learning, along with the factors influencing these outcomes. This investigation adopted a quantitative approach. The study comprised 111 students who actively participated in the academic activities during the 2021/2022 academic year, particularly those who experienced distance learning. The data underwent analysis employing descriptive statistics techniques, including the Likert scale, Likert item analysis, and examination of participants' responses to open-ended questions. The findings indicated, firstly, a notable level of student social presence in distance learning, particularly in terms of the perceived contribution of group activities to the learning process. Secondly, students exhibited a high sense of classroom community in distance learning settings, particularly in items related to connectedness. The underlying rationale for the elevated level of social presence during distance learning included each student's perception of engagement within the classroom. Similarly, the heightened sense of classroom community during distance learning stemmed from the perceived involvement of each student within the classroom environment.